1968
DOI: 10.1136/bjo.52.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcysteine in kerato-conjunctivitis sicca.

Abstract: KERATO-CONJUNCTIVITIS sicca is the condition which follows a reduction of secretion by the main and accessory lacrimal glands, and is characterized by interpalpebral staining of the bulbar conjunctiva with rose Bengal, punctate corneal staining with punctate opacities in Bowman's zone, the presence of thick stringy mucous strands in the lower fornices, and corneal filaments, the latter being neither invariable nor pathognomonic. Kerato-conjunctivitis sicca occurs most commonly as a manifestation of Sjogren's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

1969
1969
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…They reported that the healing of normal superficial epithelial ulcers is not affected by acetylcysteine. The nontoxicity and some improving effects of acetylcysteine in the present study are slightly similar to those of Absolon and Brown [4], Brown and Weller [7], Berman [11], Williamson et al [9], Frauenfelder et al [12], Marsh and Cooper [13], Burns et al [24], Sugar and Waltman [16] and Petroutsos et al [15].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They reported that the healing of normal superficial epithelial ulcers is not affected by acetylcysteine. The nontoxicity and some improving effects of acetylcysteine in the present study are slightly similar to those of Absolon and Brown [4], Brown and Weller [7], Berman [11], Williamson et al [9], Frauenfelder et al [12], Marsh and Cooper [13], Burns et al [24], Sugar and Waltman [16] and Petroutsos et al [15].…”
Section: Discussionsupporting
confidence: 76%
“…Its efficiency was confirmed in a study that found NAC to be the least irritant and the most stable one among several sulfhydryl agents [3]. Because of its mucolytic and anticollagenolytic properties, NAC has been used in ophthalmology to treat corneal diseases, such as keratoconjunctivitis sicca, filamentary keratitis, corneal mucous plaques and alkali-burned corneas [4][5][6][7][8][9][10][11][12][13]. Corneal toxicity of NAC was observed after intracorneal injection [14].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whereas collagenolytic and gelatinolytic activity is essential for tissue remodeling and wound healing, downregulation of the response is essential to maintain tissue stability after initial wound healing [11] . Because of its mucolytic and anticollagenase properties, N-acetylcysteine (NAC) has been used in ophthalmology to treat corneal diseases, such as keratoconjunctivitis sicca, filamentary keratitis, corneal mucous plaques and alkali-burned corneas [12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand, the side effects of the drug have not been thoroughly investigated [Laibson, 1980;Absolon and Brown, 1968;Sugar and Waltman, 1972],…”
Section: Introductionmentioning
confidence: 99%